APPLICATION OF CAESAR CIPHER CRYPTOGRAPHY TO ENCRYPT MESSAGES USING C++ PROGRAMMING LANGUAGE - Rayhan Anugrah Ramadhan (Journal Collabits, 2025)
Cryptography is a method used to maintain the confidentiality and integrity of messages. One of the simple but effective cryptographic techniques is the Caesar Cipher. Caesar Cipher is a character replacement algorithm that uses shifts or shifts in the alphabet. This study aims to apply the Caesar Cipher in encrypting messages. The research method used is experimentation by implementing the Caesar Cipher algorithm using the C++ programming language. Testing is done by encrypting text messages that are given using a certain shift or shift. The results showed that the implementation of Caesar Cipher cryptography succeeded in encrypting messages properly. Entered text messages are converted into encrypted forms that can only be read by recipients who have the same shift key. Message security depends on the strength of the shift key used.Keywords: cryptography, Caesar Cipher, encryption, messages, security, C++